2019
DOI: 10.1002/cam4.2407
|View full text |Cite
|
Sign up to set email alerts
|

Rational application of the first‐line chemotherapy and immune checkpoint inhibitors in advanced nonsmall cell lung cancer: A meta‐analysis

Abstract: Objective To compare the relative efficacy of immune checkpoint inhibitors (ICIs) or chemotherapy (CT) alone, or their combination modality in the first‐line treatment of advanced nonsmall cell lung cancer (NSCLC). Methods This meta‐analysis was performed on the eligible randomized controlled trials (RCTs) after searching web databases and meeting abstracts. The main research endpoints were the comparisons of median overall survival (mOS), the OS rate of 6 months (OSR6m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Chemotherapy combined with immunotherapy has become the current standard care for patients with negative oncogenic drivers regardless of squamous or non-squamous NSCLC or programmed death ligand 1 (PD-L1) expression level [ 18 ]. However, chemotherapy plus bevacizumab is still an important first-line treatment option for patients with oncogenic driver negative NS-NSCLC who cannot tolerate immunotherapy, and is also a subsequent treatment for patients with oncogenic driver positive NS-NSCLC whose disease progressed on prior targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy combined with immunotherapy has become the current standard care for patients with negative oncogenic drivers regardless of squamous or non-squamous NSCLC or programmed death ligand 1 (PD-L1) expression level [ 18 ]. However, chemotherapy plus bevacizumab is still an important first-line treatment option for patients with oncogenic driver negative NS-NSCLC who cannot tolerate immunotherapy, and is also a subsequent treatment for patients with oncogenic driver positive NS-NSCLC whose disease progressed on prior targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analysis [9,10] have directly compared the response of platinum-based chemotherapy regimens and most of them found negative results for advanced NSCLC. The response and long-term prognosis of the above regimens are similar.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses have directly compared the response of platinum-based chemotherapy regimens, and most of them found negative results for advanced NSCLC [9,10]. However, not all the chemotherapy regimens were directly compared by prospective randomized controlled trials or meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy combined with immunotherapy has become the current standard care for patients with negative oncogenic drivers regardless of squamous or non-squamous NSCLC or PD-L1 expression level [18]. However, some studies show that chemotherapy combined with the immunotherapy used in KEYNOTE-189 or IMpower150 trial is not cost effective [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies show that chemotherapy combined with the immunotherapy used in KEYNOTE-189 or IMpower150 trial is not cost effective [19,20]. Several meta-analyses demonstrated that immunotherapy combined with chemotherapy led to more toxicities as grade ≥ 3 TRAEs and more discontinuation of treatment than chemotherapy alone [18,21]. In fact, chemotherapy plus bevacizumab is still an important rst-line treatment option for patients with oncogenic driver negative NS-NSCLC who cannot tolerate immunotherapy, and is also a subsequent treatment for patients with oncogenic driver positive NS-NSCLC whose disease progressed on prior targeted therapy.…”
Section: Discussionmentioning
confidence: 99%